Non‐tuberculous mycobacteria in lung transplant recipients: Prevalence, risk factors, and impact on survival and chronic lung allograft dysfunction. Issue 2 (16th December 2019) - Friedman, Daniel Z. P.; Cervera, Carlos; Halloran, Kieran; Tyrrell, Gregory; Doucette, Karen
Abstract: Background: Non‐tuberculous mycobacteria (NTM) are environmental organisms that colonize or infect lung transplant recipients. Because of differences in populations studied and geographical diversity of species, risk factors for infection and its impact on patient outcomes post transplant are conflicting in the literature. Methods: We reviewed the charts of 375 lung transplant recipients at the University of Alberta Hospital (Edmonton, Canada) between 2005 and 2014 to assess NTM epidemiology and risk factors. NTM positivity was determined from a laboratory database. The impact of NTM on patient and graft survival was tested by multivariate Cox regression analysis. Results: Non‐tuberculous mycobacteria were cultured from 26 patients before and 17 patients after transplant. The most commonly isolated species were Mycobacterium avium complex (55%) and Mycobacterium abscessus (20%). Five‐year mortality was significantly higher in those infected with NTM after transplant ( P  = .016), but there was no difference in chronic lung allograft dysfunction (CLAD) at 5 years ( P  = .999). Cystic fibrosis and lower body mass index were associated with pre‐transplant but not post‐transplant NTM. Conclusions: Isolation of NTM occurred in 7% of patients before and 4.5% of patients after transplant. In this cohort, NTM isolation was associated with increased risk of death but not CLAD onset at 5 years.